Meeting with Elected Officials - Ricky W. Telg; Shelli Rampold (EDIS)
This 3-page document is one in a series on communicating with policymakers and elected officials, and discusses strategies for meeting with elected officials. Written by Ricky Telg and Shelli Rampold and published by the UF/IFAS Department of Agricultural Education and Communication, January 2019. http://edis.ifas.ufl.edu/wc318